1997
DOI: 10.1074/jbc.272.7.4245
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Change Responsible for AT1 Receptor Activation Is Dependent upon Two Juxtaposed Asparagine Residues on Transmembrane Helices III and VII

Abstract: A model of the angiotensin AT 1 receptor and site-directed mutagenesis were used to identify key residues involved in ligand binding. We propose that substitution of these residues causes the loss of an interaction between transmembrane helices III and VII, which allows the AT 1 receptor to "relax" into its active conformation.The renin-angiotensin system plays a vital role in the regulation of cardiovascular function, and its activity may be abnormal in a number of disease states. The effector molecule of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
89
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 43 publications
10
89
1
1
Order By: Relevance
“…This, in turn, triggers cell growth and constriction (Vincentini & Villereal, 1986). The initial AT 1 receptor-evoked responses can conveniently be measured in primary cell cultures and in cell lines (Dickinson et al, 1994;Koh et al, 1994;Panek et al, 1995;Perlman et al, 1995;Balmforth et al, 1997) and appear to be common to the biological actions of angiotensin II. In addition, it was also observed by Dickinson et al (1994) that angiotensin II increases the rate at which rabbit aortic smooth muscle cells acidify their environment with products of their energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, triggers cell growth and constriction (Vincentini & Villereal, 1986). The initial AT 1 receptor-evoked responses can conveniently be measured in primary cell cultures and in cell lines (Dickinson et al, 1994;Koh et al, 1994;Panek et al, 1995;Perlman et al, 1995;Balmforth et al, 1997) and appear to be common to the biological actions of angiotensin II. In addition, it was also observed by Dickinson et al (1994) that angiotensin II increases the rate at which rabbit aortic smooth muscle cells acidify their environment with products of their energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…B a s e d o n a n u m b e r o f pharmacological, mutagenesis and computer-oriented modeling studies [63][64][65][66][67][68][69][70][71][72][73][74][75][76], the general agreement is that a positively-charged residue of Lys199 on transmembrane domain (TM)-5 of the AT1 receptor interacts with the -carboxyl group of Phe8 in Ang II. This interaction is crucial for high affinity binding of Ang II to the receptor.…”
Section: Functional Domains Of the At1 Receptormentioning
confidence: 99%
“…67 It has been suggested that a specific interaction between the third and the seventh transmembrane helixes may be a major determinant of AT 1 receptor isomerization from an inactive to active conformation. 68 Binding of a5b1 to urokinase-type plasminogen activator receptors causes a change in the conformation to block the functions of this complex by short b1-chain peptides without affecting a5b1-mediated fibronectin binding. 69 Therefore, the decoy peptide blunted the interaction of renin with (P)RR possibly by changing specific space within the receptor.…”
Section: Interference Of Renin Binding To (P)rr By the Decoymentioning
confidence: 99%